Organizational practices and research culture factors affecting research performance in universities - Ab Rahman, Suhaimi; Esam, Asrizam; Zawawi, Dahlia; Sazili, Awis Qurni; Ismail, Nik Rosniwati; Tugiran, Yusnita; Yusof, Yushaida; Kamarudin, Norliyana (2019)
Organizational practices and research culture in universities is different in every universities that reflected the gap among universities performance in research reported by the Ministry of Education in Malaysia. Publication is one of the principle research output to be measure as a main indicator in research performance despite the fact that not the majority of the universities in Malaysia achieve in publishing journals. What are the critical factors that organizational practices and research culture in universities affecting research performance? This study explores the critical factors that influence organizational practices and research culture among scholar that affect the research performance based on faculties in Universiti Putra Malaysia, one of best research university in Malaysia. Experience exploration from 40 researchers with different rank and backgrounds of expertise, divided into science and technology, social science, art and humanities deeply investigate through the seven group discussion. Perspectives and experience from the research practitioner is most significant and crucial factors that influence their research performance. This study demonstrates common and uncommon possible tangible and intangible crucial factors that affected to research performance among the scholarly. Principally, it expands the literature, by giving further comprehension on the issues of organizational practices and research culture on the Malaysian public universities.